Експериментально-аналітичне визначення параметрів зношування та витривалості авіаційних матеріалів - Приймаков, Олександр Григорович; Приймаков, Григорій Олександрович; Градиський, Юрій Олександрович; Бобровицький, О. В. (НТУ "ХПІ", 2004)
Intensity of wear (I) and coefficient of friction (μ) of most typical aviation construction high-alloyed and heat-resistant steels 40ХНМА, Х17Н2, 30ХГСНА (DSTU 4543 - 94) are experimentally defined. It is shown, that intensity of wear can be integral index of endurance of aviation construction steels, that allows to determine simultaneously parameters of wearproof and endurance.
Keywords: працездатність авіаційних матеріалів; літальні апарати; високолеговані конструкційні сталі; коефіцієнт тертя; інтенсивність зношування; термообробка сталей